Student's View of the Penghianatan G30S/PKI Film - Albyanka Romero Himawan; Nala Nandana Undiana (Universitas Pendidikan Indonesia, 2021)
This journal discusses Pengkhianatan G30S/PKI movie and its influence on student views. Gerakan 30 September 1965 was a complex event, seven high-rangking military officers as well as several others were killed in a coup attempt. Orde Baru through Arifin C. Noer, made a propaganda film about these events from Soeharto’s perspective. From 1984 to 1998, this film became mandatory. However, until the following years, the national television station still showed this film, bringing a gymnastic influence to the next generation. Through the hypodermic needle theory, it will be examined how the effect of Pengkhianatan G30S/PKI movie for students who are hailed as agents of change, whether individuals are passive, accept all information obtained through the media, or create critical ones and see various alternative sources? This study uses a mixed descriptive method approach, the data taken is in the form of a survey with a questionnaire aimed at students who are then discussed through literature studies. Based on the research results, it was found that the students’ views were in line with the propaganda in Pengkhianatan G30S/PKI movie, especially regarding general depictions, storylines and characterizations. This is proof that the hypodermic needle theory is still valid. Meanwhile, for the post-G30S events, ignorance about this matter is still lingering. The events that are described holistically in the film are students’ views of the continuity of events. Keywords — influence, movie G30S/ PKI, Student